Endogenous retrovirus-encoded Syncytin-2 contributes to exosome-mediated immunosuppression of T cells. Issue 1 (18th July 2019) - Lokossou, Adjimon G; Toudic, Caroline; Nguyen, Phuong Trang; Elisseeff, Xavier; Vargas, Amandine; Rassart, Éric; Lafond, Julie; Leduc, Line; Bourgault, Steve; Gilbert, Caroline; Scorza, Tatiana; Tolosa, Jorge; et al.
Abstract: Modulation of the activation status of immune cell populations during pregnancy depends on placental villous cytotrophoblast (VCT) cells and the syncytiotrophoblast (STB). Failure in the establishment of this immunoregulatory function leads to pregnancy complications. Our laboratory has been studying Syncytin-2 (Syn-2), an endogenous retroviral protein expressed in placenta and on the surface of placental exosomes. This protein plays an important role not only in STB formation through its fusogenic properties, but also through its immunosuppressive domain (ISD). Considering that Syn-2 expression is importantly reduced in preeclamptic placentas, we were interested in addressing its possible immunoregulatory effects on T cells. Activated Jurkat T cells and peripheral blood mononuclear cells (PBMCs) were treated with monomeric or dimerized version of a control or a Syn-2 ISD peptide. Change in phosphorylation levels of ERK1/2 MAP kinases was selectively noted in Jurkat cells treated with the dimerized ISD peptide. Upon incubation with the dimerized Syn-2 ISD peptide, significant reduction in Th1 cytokine production was further demonstrated by ELISA and Human Th1/Th2 Panel Multi-Analyte Flow Assay. To determine if exosome-associated Syn-2 could also be immunosuppressive placental exosomes were incubated with activated Jurkat and PBMCs. Quantification of Th1 cytokines in the supernatants revealed severe reduction in T cell activation. Interestingly, exosomes from Syn-2-silenced VCT incubated with PBMCs were less suppressive when compared with exosome derived from VCT transfected with control small interfering RNA (siRNA). Our results suggest that Syn-2 is an important immune regulator both locally and systemically, via its association with placental exosomes. Abstract : Summary sentence : Human endogenous retroviral Syncytin-2 negatively downmodulates Th1 response via its immunosuppressive domain and acts through its association to exosomes.